Is it desirable for Asian economies to hold more Asian assets in their foreign exchange reserves? The People's Republic of China's answer - Bin Zhang (Asian Development Bank Institute (ADBI), 2011)
We calculate the return on the major Asian currency denominated long-term government bonds in terms of a basket of the People's Republic of China's (PRC) imports of goods and services, namely the real return on those assets from the PRC's perspective. In the sample period of January 2002 to December 2009, the real return on United States (US) treasury bills is lower than that of Japan, India, the Republic of Korea, Singapore, or Thailand's government bonds, and a little higher than that of Malaysia's government bonds. This result shows that it is desirable for the PRC to substitute Asian currency denominated government bonds for US Treasury bills to maintain the purchasing power of its foreign exchange reserves. To some extent, this research supports the proposal by Fan, Wang, and Huang (2010) on the cross holding of regional currencies in foreign exchange reserves.
Keywords: F31; F21; G11; 330; Reservewährung; US-Dollar; Vergleich; Währung; Asien; Kaufkraftparität; Währungsreserven; China